RISK MANAGEMENT AND CASH WAQF DEVELOPMENT STRATEGY IN ISLAMIC MICROFINANCE INSTITUTIONS: EMPIRICAL EVIDENCE FROM EAST JAVA MAWAR COOPERATIVE: RISK MANAGEMENT AND CASH WAQF DEVELOPMENT STRATEGY IN ISLAMIC MICROFINANCE INSTITUTIONS: EMPIRICAL EVIDENCE FROM EAST JAVA MAWAR COOPERATIVE - Khotib Khotib; Ariefah Sundari; Siti Lathifatus Sun'iyah (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2025)
This study examines risk management and cash waqf development strategies in Islamic microfinance institutions, with empirical evidence from the Mawar Cooperative in East Java. The background of this research stems from the growing importance of cash waqf as a sustainable financial instrument in Islamic finance, particularly in microfinance institutions that aim to balance social and economic objectives. The Mawar Cooperative, as a registered nazhir (waqf manager), has successfully managed and developed cash waqf through direct and indirect investments, demonstrating a unique model for other institutions. The objective of this study is to analyze the risk management practices and strategic approaches employed by the Mawar Cooperative in optimizing cash waqf for community development. Using a qualitative case study method, the research collects data from financial reports, waqf distribution records, and interviews with cooperative stakeholders. The findings reveal that the Mawar Cooperative employs a dual investment strategy—direct investments in member financing and indirect investments through partnerships with Islamic financial institutions—to mitigate risks and ensure sustainable returns. The discussion highlights the cooperative’s adherence to regulatory frameworks, transparency, and innovative waqf utilization in education, da’wah, and economic empowerment. The novelty of this study lies in its empirical focus on a microfinance institution’s role in cash waqf management, offering practical insights for policymakers and Islamic financial entities. The study concludes that effective risk management and strategic waqf development can enhance financial sustainability and social impact, providing a replicable model for similar institutions.